Genome‐wide identification and expression analysis reveal the potential function of ethylene responsive factor gene family in response to Botrytis cinerea infection and ovule development in grapes (Vitis vinifera L.). (13th December 2018) - Zhu, Y.; Li, Y.; Zhang, S.; Zhang, X.; Yao, J.; Luo, Q.; Sun, F.; Wang, X.
Abstract: The prevention of Botrytis cinerea infection and the study of grape seedlessness are very important for grape industries. Finding correlated regulatory genes is an important approach towards understanding their molecular mechanisms. Ethylene responsive factor (ERF) gene family play critical roles in defence networks and the growth of plants. To date, no large‐scale study of the ERF proteins associated with pathogen defence and ovule development has been performed in grape ( Vitis vinifera L.). In the present study, we identified 113 ERF genes ( VvERF ) and named them based on their chromosome locations. The ERF genes could be divided into 11 groups based on a multiple sequence alignment and a phylogenetic comparison with homologues from Arabidopsis thaliana . Synteny analysis and Ka/Ks ratio calculation suggested that segmental and tandem duplications contributed to the expansion of the ERF gene family. The evolutionary relationships between the VvERF genes were investigated by exon–intron structure characterisation, and an analysis of the cis ‐acting regulatory elements in their promoters suggested potential regulation after stress or hormone treatments. Expression profiling after infection with the fungus, B. cinerea, indicated that ERF genes function in responses to pathogen attack. In addition, the expression levels of most ERF genes were much higher during ovule development in seedless grapes, suggesting a role in ovule abortion related to seedlessness. Taken together, these results indicate that VvERF proteins are involved in responses to Botrytis cinerea infection and in grape ovule development. This information may help guide strategies to improve grape production.